2018
DOI: 10.1111/php.12908
|View full text |Cite
|
Sign up to set email alerts
|

Orobanche cernua Loefling Attenuates Ultraviolet B‐mediated Photoaging in Human Dermal Fibroblasts

Abstract: UV radiation is the primary cause of skin photoaging, which results in an increase in matrix metalloproteinases and degradation of collagen. Developing new natural antioxidant as photoprotective agents has become a popular area of research. Orobanche cernua Loefling is a parasitic plant that is rich in phenylethanoid glycosides (PhGs). This study investigated the photoprotective effects of the ethanolic extract of Orobanche cernua Loefling (OC) and its principal component acteoside on UVB-induced photoaging as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Human dermal fibroblasts (HDFs)‐adult were obtained from ScienCell Research Laboratories (Cat.2320, Carlsbad, CA). As described in our previous study, the cells were cultured in DMEM supplemented with 10% heat‐inactivated FBS and 1% penicillin–streptomycin (18). The HDFs cells that we have used in our experiments were no more than the 10 th cell passage.…”
Section: Methodsmentioning
confidence: 99%
“…Human dermal fibroblasts (HDFs)‐adult were obtained from ScienCell Research Laboratories (Cat.2320, Carlsbad, CA). As described in our previous study, the cells were cultured in DMEM supplemented with 10% heat‐inactivated FBS and 1% penicillin–streptomycin (18). The HDFs cells that we have used in our experiments were no more than the 10 th cell passage.…”
Section: Methodsmentioning
confidence: 99%
“…Photoaging is a process mainly triggered by ultraviolet radiation from chronic sun exposure that leads to DNA damage and the production of reactive oxygen species, which both promote inflammation [ 159 ] and result in increased matrix metalloproteinases (MMPs) and collagen degradation [ 160 ]. Retinoids have demonstrated efficacy in the treatment of the photoaged skin.…”
Section: Immunomodulatory Effect Of Ra During Inflammatory Processmentioning
confidence: 99%
“…Gao et al found O. cernua extract and acteoside ( 10 ) to exhibit strong scavenging effects with IC 50 values of 56.3 µg/mL and 20.6 µg/mL, respectively. No standard deviations of the measured values were given [ 100 ]. Antioxidant activities of O. crenata and O. foetida methanolic and aqueous extracts was tested by Abbes et al using DPPH and ABTS (2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activity assays.…”
Section: Resultsmentioning
confidence: 99%
“…Levels of cytoprotective agents HO-1 and NQO-1 were increased by O. cernua extract and acteoside, hereby increasing protection against UVB-induced oxidative stress through activation of the cutaneous endogenous antioxidant system. UVB-induced enhacement of Smad7 expression and decrease of Smad2/phosphorylation were reversed by O. cernua extract and acteoside ( 10 ), and TGF-β1 expression was enhanced, hereby repairing the TGF-β/Smad signaling pathway and enhancing type-I procollagen synthesis [ 100 ]. (No standard deviations of the measured values described above were indicated.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation